Homemade formulas for nutrition support in chronic kidney disease: A narrative review of the opportunity for education, research, and innovation - Brandon M. Kistler; Annabel Biruete; Wong, Michelle M. Y.; Wang, Angela Yee‐Moon; Fabiola Martin‐del‐Campo; Fabiana B. Nerbass; Anna Hardy; Qiwei Zhu; Khor, Ban Hock; Lloyd Vincent; Zarina Ebrahim; Ana Figueiredo (American Society for Parenteral and Enteral Nutrition, 2025)
Protein-energy wasting is common in people with chronic kidney disease (CKD), especially in those undergoing kidney replacement therapy. Oral nutrition supplements and enteral nutrition are strategies that have been shown to improve nutrition status, and potentially outcomes. However, access to specialized commercial products for people with CKD is limited by factors including cost and regional availability. Homemade formulas represent a potentially cheaper, accessible, and more flexible option than commercial products, but they come with their own unique set of challenges. Furthermore, some aspects of homemade products, including consistency of nutrients, physical properties, and food safety, may pose challenges in the context of physiological changes that occur in CKD. Despite evidence of their use in CKD clinics, there have been few studies using homemade formulas in this population. This narrative review article summarizes the available literature on the potential usage, benefits, and concerns related to homemade formulas, emphasizing the unique challenges in people with CKD. Given the potential usage and limited research on homemade formulas in people with CKD, additional education and research are warranted to optimize the use of these tools in this clinical population.